The dyslexic advantage : unlocking the hidden potential of the dyslexic brain - Eide, Brock, 1962-; Eide, Fernette, 1961- (Plume, 2023)
"An updated edition of Drs. Brock and Fernette Eide's popular dyslexia book with a wealth of new material and improved dyslexic-friendly font"--